Dysydent Bogdan Radica - Czerwiński, Maciej (Wydawnictwo Nauka i Innowacje, 2014)
In the article a certain prominent Croatian emigrant, but very little known in Croatia, is taken into consideration. Bogdan Radica (1904–1993) was a political dissident in two different circumstances. Between 1941–1945, as an attaché of the Yugoslav Embassy in Washington, he was opposing both the Ustasha’a Croatian state and Yugoslav policy under Serbian control, which he defined as a hegemonic and ‘anti-Yugoslav’. Between 1945–1993, with a short period supporting the Communists, he became the most prominent representative of the Croatian emigration, emphasizing pro-independent attitudes. His engagement is seen not as an ideological profile but as an attitude.
A Dissident Bogdan Radica
Keywords: Bogdan Radica; Croatian emigration; exile; liberal thought; independence; communism; fascism; dissidence